USE OF RESIDUES FROM FRUIT TRANSFORMATION FOR THE PREPARATION OF BIOPACKAGE - Ubaque Beltrán, Camila Andrea
The objective of the research was to develop a bio-packaging as an alternative in the use of polyethylene for the production of synthetic packaging. In this sense, Lorena variety avocado seed of Colombian origin was used, where the seed remains as a residue after its transformation process in culinary, pharmaceutical, aesthetic processes, etc. Additionally, to help mitigate the environmental impact. The starch extraction method applied was through decantation and drying at 60 ° C. Then physicochemical and microbiological analyzes were carried out, resulting in 9% humidity, 75% starch content, 55 ° C Gelatinization temperature, Ash 0.3, 4.5 pH and the count of molds and yeasts 500 CFU / g, aerobic mesophylls 10,300 CFU / g, E.coli <10 CFU / g and detection of Salmonella Absent / 25g, complying with current regulations. Demonstrating that bio-packaging with the addition of ethanolic extract of propolis is a promising conservation alternative for blackberries, extending their useful life.